The Role of Cannabinoid Receptors in Renal Diseases - Francois, Helene; Lecru, Lola (Current Medicinal Chemistry, 2018)
Background: Chronic kidney disease (CKD) remains a major challenge for Public Health systems and corresponds to the replacement of renal functional tissue by extra-cellular matrix proteins such as collagens and fibronectin. There is no efficient treatment to date for CKD except nephroprotective strategies. The cannabinoid system and more specifically the cannabinoid receptors 1 (CB1) and 2 (CB2) may represent a new therapeutic target in CKD. Methods: We performed PubMed searches using the terms “cannabinoid receptors” in combination with “kidney” or “renal disease” or “nephropathy” or “diabetes” or “renal fibrosis” or “cellular pathways” in various combinations. We analyzed full-text English-language papers. We also searched the reference lists of identified articles for further relevant papers. Results: We gathered data regarding the current state of knowledge on the cannabinoid system in normal renal physiology and in various experimental nephropathies, especially diabetes. We also reviewed data obtained in models of diabetes and obesity as well as in non metabolic models of renal fibrosis when CB1 blockers and/or CB2 agonists were used. We also found that very few data are available so far regarding the cellular pathways involved downstream of the cannabinoid receptors in the development of renal fibrosis. Conclusion: Overall, we found that the cannabinoid receptors are a promising target in the development of renal disease and fibrosis, particularly in CKD and diabetes.
Keywords: renal fibrosis